2019
DOI: 10.9778/cmajo.20190092
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ information needs and preferences related to bronchiolitis: a qualitative study

Abstract: Bronchiolitis, an acute lower respiratory tract infection, affects more than one-third of children less than age 2 years and is the most common cause for hospital admission in the first year of life. 1 Respiratory syncytial virus is the most common cause of bronchiolitis. The condition is characterized by inflammation and edema in the small airways, with increased mucus production. 2 Although most instances of bronchiolitis are self-limiting, severe complications, such as pneumonia and empyema, may occur. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
(28 reference statements)
4
16
0
4
Order By: Relevance
“…Some of our findings agreed with a qualitative study by Campbell et al, which explored parental preferences for information on bronchiolitis in the ED 27 . Indeed, this study also found that most parents reported receiving insufficient information on how to recognise the symptoms of bronchiolitis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some of our findings agreed with a qualitative study by Campbell et al, which explored parental preferences for information on bronchiolitis in the ED 27 . Indeed, this study also found that most parents reported receiving insufficient information on how to recognise the symptoms of bronchiolitis.…”
Section: Discussionsupporting
confidence: 91%
“…None of the tools were prepared by our healthcare institution. Moreover, previous studies that have evaluated parents’ preferred methods of information on bronchiolitis yielded similar findings in different settings, suggesting some validity in the overall identified themes 17,27 . Lastly, we were unable to collect data from parents who refused to participate in the study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Findings from this study and our study exploring parents’ information needs and preferences related to bronchiolitis ( 13 ) will inform the development of digital KT tools for parents of children with bronchiolitis. Parent experiences will be used to create a narrative for the digital KT tool.…”
Section: Practice Implicationsmentioning
confidence: 92%
“…The aim of this qualitative study was to describe parents’ experiences caring for a child with bronchiolitis and identify their information needs managing bronchiolitis. The information needs identified by parents are reported elsewhere ( 13 ). Here, we explicitly report on the overall daily experience of parents caring for a child with acute bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%